The Penetration of Business Information Systems in Small and Medium-sized Enterprises in Italy and Hungary: A Comparative Study - Selena Aureli; Massimo Ciambotti; Péter Sasvári (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
Information technology (IT) has become an integral part of an enterprise's organizational life recently and represents an increasingly important factor for all kinds of organizations, since the services it provides have become almost essential by now for all types of enterprises in the European Union. However, company size and differences at country level might still play an important role in hindering IT adoption. The main reason for writing this article was to analyse IT penetration and usage in Italy and Hungary and find a well-grounded answer to the question of whether IT – in the form of business information systems – is regarded as a source of competitive edge or an essential condition for survival by different enterprises in different countries. To explore this topic, a survey was conducted by submitting an online questionnaire to a sample of Italian and Hungarian enterprises. The results indicate a noticeable difference in the IT development level of the two countries. In Italy information systems in general and systems for managers decision-making are more widespread, thus IT has already reached the level of an essential condition for survival there, whereas it is still seen as a source of competitive edge in Hungary. However, contrary to our initial assumption, the question of competitive edge versus condition for survival depends more on size categories rather than on individual countries.
Keywords: M15; M21; 330; business information systems; information technology; microenterprises; small and medium-sized enterprises; Hungary; Italy; IT penetration